PERLINDUNGAN HUKUM BAGI UPAH PEKERJA AKIBAT PANDEMI COVID-19 DALAM PERSPEKTIF MAQASHID SYARIAH (Program Studi Muamalah Fakultas Syariah dan Hukum, 2022)
Based on the results of the study, it can be concluded that: First, in the Circular Letter of the Ministry of Manpower Number M/3/HK.04/III/2020, workers/labourers affected by thePandemic Covid-19 such as ODP (People Under Supervision), PDP (Internal Patients) treatment), or patients who are positive for corona are entitled to wages. Second, the theory in Maqashid Syariah there are five basic basic needs, namely: religion (hifdẕu-din), soul (hifdẕu-nāfs), reason (hifdẕu al-'aql), offspring (hifdẕu nāsl), and property (hifdẕu-māl). . ThePerspective Maqashid Syariah for Legal Protection of Workers Due to the Covid-19 Pandemic has fulfilled the benefit of property (hifdẕu-māl) and contains hifdẕu-nāfs (protection of life). The research method used in this research is Library Research with library materials sources, data collection techniques through several books, legal magazines, legislation and other documents related to the discussion. Then the data were analyzed using descriptive analysis.